A systematic review and meta-analysis of fractional dose compared to standard dose inactivated polio vaccination in children - Mashunye, Thandiwe Runyararo (Department of Public Health and Family Medicine, 2020)
The World Health Organisation (WHO) recommends the introduction of at least one single dose of inactivated polio vaccine (IPV) in routine immunisation schedules to mitigate the risk of a polio virus type 2 reintroduction or re-emergence. As a result, there has been an increased demand and concurrent supply shortages of IPV worldwide resulting in poor access to IPV. With the phasing out of the oral polio vaccine and the pursuit of global eradication of polio, ensuring an adequate supply of IPV is of paramount importance. One of the strategies to improve access is the use of the fractional dose because of its dose sparing and cost reduction properties. This mini-dissertation presents a research protocol (Section A), scoping review (Section B) and journal formatted manuscript (Section C) for a systematic review and meta-analysis of fractional dose compared to standard dose inactivated polio vaccination in children. Section A describes the rationale for the review, eligibility criteria, the search strategy and methods for data extraction and analysis. Section B is a scoping review that details the journey towards eradication of polio, the current state of IPV demand and supply and further explains the rationale for performing the systematic review. Section C is a manuscript that gives the results of the review after performing the methods outlined in Section A. The results showed that as the number of IPV doses increased the seroconversion rates for fractional dose and full dose IPV approximated each other such that at three doses the rates were similar. In conclusion, there is no difference in seroconversion between three doses of fractional dose IPV and three doses of full dose IPV. With the current IPV shortages, using fractional dose IPV instead of the full dose IPV can stretch supplies and possibly lower the cost of polio vaccination.